Compliance Analysis Of Hand Hygiene Regulation Implementation At Dr. M. Goenawan Partowidigdo Pulmonary Hospital Based On Who Multimodal Hand Hygiene Improvement Strategy - Mila Fitriana; Anhari Achadi; Masyitoh Bashabih; Ede Surya Darmawan; Ida Bagus Sila Wiweka (Jurnal Indonesia Sosial Teknologi, 2023)
The Hospital Infection Prevention and Control Program (HIPCP) is an effort to reduce the risk of Healthcare-Associated Infections (HAIs), including hand hygiene compliance. WHO issued the Multimodal Hand Hygiene Improvement Strategy as one of the strategies to tackle low hand hygiene compliance. Dr. M. Goenawan Partowidigdo Pulmonary Hospital (RSPG) has implemented hand hygiene regulations referring to the current policies, but it has not met the target over the last three years. This study aims to analyze the implementation of the regulation of hand hygiene compliance at RSPG according to the WHO Multimodal Hand Hygiene Improvement Strategy, using an analytical descriptive qualitative approach with a case study method. The analysis uses the combination of the theory of George Edward III, Weaver, and the WHO Multimodal Hand Hygiene Improvement Strategy. WHO Multimodal Hand Hygiene Improvement Strategy assessment was conducted by scoring the Hand Hygiene Self-Assessment Framework (HHSAF). The results showed the lowest percentage of HHSAF scores on the bureaucratic structure variable, but the most important variable was the resource variable, namely human resources, related to activeness and behavior issues. These issues were obtained from in-depth interviews developed from structured questions on HHSAF. Hand Hygiene of RSPG is at an intermediate level. Researchers recommend behavioral enforcement with appreciative inquiry in addition to reward and punishment as an effort to improve compliance with the implementation of hand hygiene regulations at RSPG.